Feedback : Kiln control. (21st March 2016) - Adams, Bob
Abstract: In reply to the feature article "Bubble signatures revealed in antique artefacts" by Stephen C Wallace and Geraldine Kenney-Wallace (January pp34–38) about how physics can help to tell a real antique porcelain object from a fake.